2011
DOI: 10.1177/003335491112600414
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure in Young People and Parental Rules against Smoking at Home and in the Car

Abstract: Young people from families that made and enforced strong rules against smoking in homes and cars were much less likely to report SHS exposure. Parents would be wise to endorse and enforce strong smoke-free policies for both homes and cars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 18 publications
1
31
4
Order By: Relevance
“…Additionally, current smokers without complete smoke-free home policies were more likely to be male and had lower confidence in quitting. Smoke-free home policies have been associated with higher confidence in quitting (Borland et al 2006;Cartmell et al 2011). Unfortunately, unlike prior research (Borland et al 2006;Clark et al 2006;Hyland et al 2009a, b), our sample did not demonstrate more recent quit attempts among those with complete smoke-free home policies.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Additionally, current smokers without complete smoke-free home policies were more likely to be male and had lower confidence in quitting. Smoke-free home policies have been associated with higher confidence in quitting (Borland et al 2006;Cartmell et al 2011). Unfortunately, unlike prior research (Borland et al 2006;Clark et al 2006;Hyland et al 2009a, b), our sample did not demonstrate more recent quit attempts among those with complete smoke-free home policies.…”
Section: Discussioncontrasting
confidence: 85%
“…Smoke-free policies in personal places such as homes and cars are associated with reduced smoking among adults and a reduction of SHSe among children and nonsmoking adults sharing those spaces (Cartmell et al 2011). Additionally, having smoke-free home policies is associated with reduced cigarette consumption, increased quit attempts, and reduced chance of relapse (Borland et al 2006;Clark et al 2006;Hyland et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are limited in that participants were not asked about tobacco policies in cars and our results do not differentiate between participants exposed in a room versus in a car. Cartmell and colleagues26 found that of students who reported exposure to SHS in one place only, two-thirds reported exposure only in the car, and prevalence of SHS exposure in cars has been shown to be higher in those with no smoke-free vehicle rules 3…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents may be susceptible to being exposed to SHS from several sources, including at school, in private cars, and at home, especially in the absence of smokefree rules (Cartmell et al, 2011;King, Dube, & Tynan, 2012;Olufajo & Agaku, 2014). The degree of overall SHS exposure among nonsmoking adolescents could reflect underlying exposure to different behavioral, environmental, and social pro-tobacco influences, such as living with a smoker or having smoking friends-factors which have been shown to predict smoking among youths (US Department of Health and Human Services, 2012).…”
Section: Introductionmentioning
confidence: 99%